Use of the gas chromatographic method for the denitrification process assessment in groundwater of the Triassic aquifer in Opole region (southern Poland) - ŻUREK, Anna; MOCHALSKI, Paweł (Geology, Geophysics and Environment, 2010)
The studied aquifer - Major Groundwater Basin (MGWB) 333 is located near Opole in Muschelkalk carbonate rocks. The hydrological conditions of the investigated area are determined by monoclinal structure of the geological formations. On the outcrop of the Muschelkalk formation, the aquifer is unconfined and the recharge rate and conductivity are relatively high. In the northern part of the aquifer, which is covered with a confining unit of the Keuper formation, the average hydraulic conductivity and the flow velocity decrease. Nitrates have been the main indicator of groundwater contamination. The high NO3 concentrations which are observed in the outcrop area decrease significantly in the zone near the border of the Kauper extent. There are two main reasons of the nitrate concentration decline: denitrification process and groundwater age. Denitrification was identified using data on dissolved gas concentrations which were detected and quantified by gas chromatographic method. The expected denitrification effects have been observed in the samples from transitional zone of the Triassic aquifer.